2015
DOI: 10.1155/2015/689375
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation of the Tinnitus Handicap Inventory with Depression and Anxiety in Veterans with Tinnitus

Abstract: Objective. The mechanisms of tinnitus are known to alter neuronal circuits in the brainstem and cortex, which are common to several comorbid conditions. This study examines the relationship between tinnitus and anxiety/depression. Subjects and Methods. Ninety-one male veterans with subjective tinnitus were enrolled in a Veterans Affairs Tinnitus Clinic. The Tinnitus Handicap Inventory (THI) was used to assess tinnitus severity. ICD-9 codes for anxiety/depression were used to determine their prevalence. Pure to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 40 publications
3
20
1
Order By: Relevance
“…Other survey instruments used were Depressive Tendency Questionnaire (DTQ), Illness Attitude Scale, Obsessive Beliefs Questionnaire-44 (OBQ-44), International Statistical Classification of Diseases 9 (ICD-9), Depression, Anxiety and Stress Scale, and Mini International Neuropsychiatric Interview [13][14][15][16][17][18][19][20][21][22][23] .…”
Section: Resultsmentioning
confidence: 99%
“…Other survey instruments used were Depressive Tendency Questionnaire (DTQ), Illness Attitude Scale, Obsessive Beliefs Questionnaire-44 (OBQ-44), International Statistical Classification of Diseases 9 (ICD-9), Depression, Anxiety and Stress Scale, and Mini International Neuropsychiatric Interview [13][14][15][16][17][18][19][20][21][22][23] .…”
Section: Resultsmentioning
confidence: 99%
“…On a national health and nutrition examination survey, hearing loss was also found to be strongly associated with depression among US adults of all ages . Tinnitus has also been associated with mental disorders in various studies with 41% to 77% of the tinnitus population presenting with psychiatric comorbidities . The incidence of depression in patients with vertiginous disorders was estimated to be 19%, and it has been shown that patients with dizziness and anxiety or depression had the highest emotional distress and handicaps .…”
Section: Introductionmentioning
confidence: 99%
“…Database Study Group, 2014;Tyler, Noble, Coelho, Roncancio, & Jun, 2015). Tinnitus handicap has been shown to be related to the loudness of tinnitus, hyperacusis, insomnia, anxiety, and depression (Hiller & Goebel 2007;Hiller & Goebel 2006;Kehrle et al 2016;Ooms et al 2012;Andersson et al 2004;Hu et al 2015;Tyler & Baker 1983;Juris et al 2013;Aazh & Allott 2016;Hebert et al 2012;Probst et al 2016;Folmer & Griest 2000). It has been suggested that anxiety symptoms are more likely to lead to depressive symptoms than depressive symptoms are to lead to anxiety symptoms (Lenze & Wetherell 2011;Wetherell et al 2001).…”
mentioning
confidence: 99%